2008
DOI: 10.1117/12.761214
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of tumor angiogenesis

Abstract: Photoacoustic imaging is a hybrid imaging modality that is based on the detection of acoustic waves generated by absorption of pulsed light by tissue chromophores such as hemoglobin in blood. Serial photoacoustic imaging has been performed over a 10-day period after subcutaneous inoculation of pancreatic tumor cells in a rat. The images were obtained from ultrasound generated by absorption in hemoglobin of short laser pulses at a wavelength of 1064 nm. The ultrasound signals were measured in reflection mode us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…16 Since aggressively growing tumors are densely vascularized, optoacoustic systems have been used in the past to image various tumors on the macroscopic and microscopic scales. [17][18][19][20][21][22][23] In cancer research using orthotopic models, in which primary tumors are induced in the internal organs and their metastases spontaneously appear in various parts of the animal body, whole-body imaging is desirable. Whole-body mouse imaging may enable the detection of tumors in internal organs, not only subcutaneous tumors.…”
Section: Introductionmentioning
confidence: 99%
“…16 Since aggressively growing tumors are densely vascularized, optoacoustic systems have been used in the past to image various tumors on the macroscopic and microscopic scales. [17][18][19][20][21][22][23] In cancer research using orthotopic models, in which primary tumors are induced in the internal organs and their metastases spontaneously appear in various parts of the animal body, whole-body imaging is desirable. Whole-body mouse imaging may enable the detection of tumors in internal organs, not only subcutaneous tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic imaging (PAI), a hybrid imaging method combining high optical absorption contrast with high ultrasound resolution, is highly desirable for vascular imaging and characterization [ 14 , 24 , 42 45 ]. In PAI, the tissue absorbs short laser pulses and generates ultrasonic waves (also known as photoacoustic (PA) waves) which can reveal the physiological information of absorbers such as blood, melanin, and water.…”
Section: Visualising the Process Of Vascularisation In Vmentioning
confidence: 99%
“…A few examples can be briefly mentioned as follows. In 2008, Kolkman et al [4] conducted a PAI study to follow the growth of pancreatic tumor cells in a rat. In 2011, Jansen et al [5] demonstrated a study on the intravascular photoacoustic imaging of human coronary atherosclerotic plaque using a custom build catheter.…”
Section: Introductionmentioning
confidence: 99%